Kodeksy etyczne polskich uczelni znajdujących się w Times Higher Education World University Rankings 2024 = Codes of ethics of polish universities included in the Times Higher Education World University Rankings 2024 - Gałat, Wioleta (Zielona Góra: Lubuskie Towarzystwo Naukowe)
The academic ethos defines the pillars of a university`s functioning, based on which specific policies and codes of ethics are adopted. The passage of time, changing institutional conditions, and external factors should not affect the university`s foundation, which consists of its constitutive values.
Keywords: university; academic ethos; code of ethics; Times Higher Education; uniwersytet; etos akademicki; kodeks etyczny